1985
DOI: 10.1177/009539978501700303
|View full text |Cite
|
Sign up to set email alerts
|

Conceptualizing Bureaucratic Responsiveness

Abstract: The concept of bureaucratic responsiveness has been utilized by scholars in contradictory and incomplete fashion. This analysis considers essential elements of the general concept of political responsiveness to provide the basis for consideration of the unique components of bureaucratic responsiveness. The problems of specifying the parameters of responsiveness under any given conceptualization are addressed as a means of delineating the bases of disagreement regarding the meaning of bureaucratic responsivenes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…Up until now, researchers have examined the responsiveness gap at the national level, associating it with such factors as the institutional design of the government, the operation of national legislatures, the presidency, interest organizations, political parties and bureaucracy . In a previous pape r, we demonstrated that the responsiveness gap can be examined at the individual level by examining the gap between what people perceive they receive (i.e.…”
Section: Introductionmentioning
confidence: 93%
“…Up until now, researchers have examined the responsiveness gap at the national level, associating it with such factors as the institutional design of the government, the operation of national legislatures, the presidency, interest organizations, political parties and bureaucracy . In a previous pape r, we demonstrated that the responsiveness gap can be examined at the individual level by examining the gap between what people perceive they receive (i.e.…”
Section: Introductionmentioning
confidence: 93%
“…In the first place, public agencies are expected to be responsive to other actors within the political system, particularly to elected politicians aiming to control their activities. They need to follow and anticipate the directions of their political masters (Saltzstein 1992;Romzek and Dubnick 1994, p. 266). Secondly, agencies providing services to members of the public are called on to be responsive to the needs of their clients in a way analogous to private sector firms being sensitive to consumer demands (Hughes 1994, pp.…”
Section: 'Accountability' and 'Responsiveness'mentioning
confidence: 99%
“…To whom, and to what, should public administrators be responsive? [12] Contrary to the impressions of some political officials, the lines of accountability and influence in a system of blended powers are not amenable to tidy division of functions and authority. Legislators may, and at times do, micro-manage agency programs and processes.…”
Section: Resultsmentioning
confidence: 97%